Diffraction of a high intensity light by ultrasound in nonlinear liquids - KOSMOL, Marek; ŚLIWIŃSKI, Antoni (Archives of Acoustics, 1979)
The paper presents some experimental and theoretical results obtained in the examination of high power light diffraction (ND^3+ laser) by ultrasound (4 MHz) in nonlinear liquids. The diffraction patterns differ from the usual results for the light of small intensity. The distributions of the light can be explained by the influence of the optical nonlinearity of the medium (3-rd harmonic light generation and frequency mixing). The theoretical description proposed appears to explain the experimental results.